Predicting the effects of time‐varying temperatures on stream invertebrate mortality - Timothy J. Cox; J. Christopher Rutherford (New Zealand Journal of Marine and Freshwater Research, 2000)
Stream managers often need to predict the impacts of high and time‐varying temperature on key stream invertebrates. A simplified model has been developed and calibrated using mortality observations made at constant temperature for two important New Zealand stream invertebrates: the snail Potamopyrgus antipodarum and the mayfly Deleatidium autumnale . A close fit was obtained for Deleatidium but Potamopyrgus showed evidence of acclimation during the 96‐h tests. The model successfully predicted the mortality observed when temperature varied diurnally by ±5°C in seven experiments but over‐estimated mortality in the eighth. The experiments used to calibrate and test the model were performed on test animals collected in winter (April‐June) and acclimated at 16–17°C. The model was less successful at predicting mortality on Deleatidium collected in summer (December‐January) and/or acclimated at 21–22°C. The likely reason is that the model, calibrated using winter data, does not account for summer acclimation.